Social media branding for small business : the 5-sources model : a manifesto for your branding revolution - Davis, Robert, 1967- (Digital and social media marketing and advertising collection., 2015)
Social media branding provides the thinking, evidence, and practice to create a road map for practitioners in small businesses to develop and implement their brand in online and offline communities. It provides a start point because one of the biggest issues for small businesses is where to start. I have talked to so many business practitioners who don't like the idea of social media. Often, they say: "We can't do that because of the legal implications!" Or, "We will have to employ more people and we don't have the resources."